Correlation of average hydrophobicity, water/air interface surface rheological properties and foaming properties of proteins - Medrano, A. (2012)
A comparative study on the behavior in the air–water interface of b-lactoglobulin, a-lactoalbumin, glycinin and b-conglycinin was performed. The behavior at the interface was evaluated by equilibrium surface tension and surface rheological properties of adsorbed films. There were significant differences (a 0.05) in the values of the constants of adsorption to the interface of the four proteins. The glycinin had the slowest rate of adsorption, due to its low average hydrophobicity, low molecular flexibility and large molecular size. Smaller proteins like b-lactoglobulin and a-lactoalbumin tended to greater equilibrium pressure values than the larger proteins because of its higher rate of adsorption to the interface. The foam capacity of proteins showed a positive correlation with the average hydrophobicity; the maximal retained liquid volume or the initial rate of passage of liquid to foam were significantly lower (a 0.05) when protein was glycinin. The dilatational modulus of glycinin was the lowest, which implies lowest resistance to disruption of the film. Glycinin protein has lower proportion of gravitational drainage and higher disproportionation having perhaps a less resistant film. In conclusion, b-conglycinin and whey proteins showed a similar behavior, so b-conglycinin might be the best soybean protein to replace milk proteins in food formulations.